The Influence of Product Quality, Product Design, Brand Image on Realme Smartphone Purchase Decisions - Akbar, Shofif Sobaruddin; Violinda, Qristin; Setiawati, Ira; Rizwan, Muhammad (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
The level of sales of realme smartphones in the low-end and mid-range segments is still inferior to other brands. This study aims to identify the influence of consumer purchasing decisions on product quality, product design, and brand image. The population in this study were all realme smartphone consumers. The number of samples in this study was 96 respondents. The sampling technique used was purposive sampling. The analysis tool used is SEM SmartPLS. This study explains that product quality directly influences 40.3% of purchasing decisions. Product design also directly influences 32.6% of purchasing decisions, while the brand image does not affect purchasing decisions. Therefore, brand image cannot mediate product quality and design on purchasing decisions. Product design directly affects 41.9% of brand image, and product quality directly affects 32.2%. Thus, it is necessary to pay attention to these three things to increase sales.